Оценка вероятностей возникновения пожаров в жилом секторе Республики Беларусь - Il'yushonok, Александр; Rusenko, Ю. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2012)
The causes are analyzed influencing the risk of fire in the residential sector in this article. Two main reasons are identified, such as “Careless handling of fire” and “Faulty design and operation of electrical equipment”. For these reasons the risk of fire in the residential sector is determined and key factors influencing its value are identified.